2011
DOI: 10.1681/asn.2010111148
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Locus Associates with Serum IgG Levels and Albuminuria

Abstract: The interaction between IgG and Fc-␥ receptors in glomeruli contributes to the development of several types of proteinuric glomerular disease, but the involvement of immunological mechanisms in hypertensive renal injury is incompletely understood. Here, we investigated serum IgG levels in SHR-A3 rats, which develop hypertensive injury, and compared them with the injury-resistant SHR-B2 line. At 18 weeks old, SHR-A3 rats had serum total IgG levels nearly twice those of SHR-B2 rats, although subclass IgG2b was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 35 publications
(31 reference statements)
0
21
0
Order By: Relevance
“…We have reported extensive functional sequence variation in the Fc region of the immunoglobulin gamma heavy chains of SHR-A3 and its association with renal injury 8 . Our analysis of the whole genome sequences for the two SHR lines reveals that the IgH locus contains extensive variation between the two SHR lines, for SHR-B2 this is the most divergent region of the entire genome 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported extensive functional sequence variation in the Fc region of the immunoglobulin gamma heavy chains of SHR-A3 and its association with renal injury 8 . Our analysis of the whole genome sequences for the two SHR lines reveals that the IgH locus contains extensive variation between the two SHR lines, for SHR-B2 this is the most divergent region of the entire genome 20 .…”
Section: Resultsmentioning
confidence: 99%
“…In SHR lines differing in CKD risk, injury susceptibility may arise within the genes participating in immune responses triggered by disturbed vascular auto-regulation. We have recently reported extensive functional natural allelic variation affecting the immunoglobulin heavy chain locus in this rat model of hypertensive renal disease 2, 8 . This variation results in functional alteration to IgG sequence that is associated with severity of albuminuria.…”
Section: Introductionmentioning
confidence: 99%
“…160,161 In addition, SHR rats develop several other phenotypes including insulin resistance, [162][163][164][165] renal damage such as mild proteinuria and albuminuria, glomerular sclerosis and pathological alterations in small vessels with age. 166,167 Cosegregation and linkage analyses Herring et al 168 investigated whether the IgG/Fc-g receptor pathway in glomeruli is capable of modulating hypertensive glomerular disease such as albuminuria in SHR. In an (SHR-A3 Â SHR-B2)-F2 intercross, the authors identified in male SHR-A3 a QTL on RNO6 linked to IgG subclasses (Tables 1 and 5), which was derived from the IgH gene (immunoglobulin heavy chain complex).…”
Section: Strain Characteristicsmentioning
confidence: 99%
“…In an (SHR-A3 Â SHR-B2)-F2 intercross, the authors identified in male SHR-A3 a QTL on RNO6 linked to IgG subclasses (Tables 1 and 5), which was derived from the IgH gene (immunoglobulin heavy chain complex). 168 Subsequently, single-nucleotide polymorphism genotyping revealed that allelic variation in the IgH haplotype block or neighboring genes may modify the susceptibility to hypertensive renal injury without a BP influence. 168 …”
Section: Strain Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation